Navigasi Ketat di Lautan Risiko: Menggali Dinamika Kepatuhan Prinsip Kehati-Hatian Perbankan di Era Ekonomi Digital Indonesia - Eleos T, Maria; Safira F, Amelinda; Ariani P, Natalia; S, Suwarsit (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The digital economy era has fundamentally transformed the landscape of the Indonesian banking industry, presenting new challenges in the application of the banking prudential principle. This study explores the dynamics of regulatory compliance in the digital era, with a particular focus on the implementation of Regulatory Technology (RegTech) and the role of regulatory sandboxes in mitigating the risks of financial innovation. Through a comprehensive analysis of Bank Indonesia and Financial Services Authority policies, this study reveals how regulators adapt their supervisory frameworks to accommodate technological developments such as mobile banking and financial technology (fintech), while maintaining the integrity of the financial system.The findings show that RegTech has become a vital instrument in bridging the gap between digital innovation and regulatory compliance. The implementation of regulatory sandboxes as testing laboratories for financial innovation provides a balance between encouraging innovation and protecting system stability. The study finds that the success of adapting the prudential principle in the digital era depends on three main pillars: (1) effective implementation of RegTech, (2) a robust regulatory sandbox framework, and (3) comprehensive digital security standardization. Through the integration of these three elements, regulators have succeeded in creating an ecosystem that supports innovation while minimizing systemic risk. However, challenges such as the technological gap between institutions and the need to improve digital competencies still require special attention.